2020
DOI: 10.3389/fenvs.2019.00207
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Determinants of Land Use/Cover Change in Wetlands in East Africa: A Case Study Analysis of the Anyiko Wetland, Kenya

Abstract: In East Africa, wetlands are steadily converted to agriculture for food security reasons. This study analyzed high spatial resolution panchromatic and color photographs in the Anyiko wetland in Kenya to reveal wetland conversions between 1966 and 2018. In addition, socioeconomic determinants of land use/cover change are assessed in the Anyiko wetland. Socioeconomic data was collected through a questionnaire survey of 226 households. A Chi-squared Automatic Interaction Detector (CHAID) decision tree approach is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 49 publications
(74 reference statements)
2
17
0
Order By: Relevance
“…The finding agrees with the national environmental management authority (NEMA) district environmental action plan of Trans Nzoia county, which documented encroachments on protected areas by the locals to boost their household food production (GOK 2019). Similarly, Maua et al (2022) and Ondiek et al (2020) observed that the rich wetland resources of the Nzoia and Lake Victoria drainage systems experienced rampant anthropogenic exploitation within the period under our study. Studies in Kenya have also attributed cropland expansion to agricultural extensification practices (Eckert et al 2017;Mwangi et al 2018).…”
Section: Lulc Changes and Cropland Expansionsupporting
confidence: 68%
“…The finding agrees with the national environmental management authority (NEMA) district environmental action plan of Trans Nzoia county, which documented encroachments on protected areas by the locals to boost their household food production (GOK 2019). Similarly, Maua et al (2022) and Ondiek et al (2020) observed that the rich wetland resources of the Nzoia and Lake Victoria drainage systems experienced rampant anthropogenic exploitation within the period under our study. Studies in Kenya have also attributed cropland expansion to agricultural extensification practices (Eckert et al 2017;Mwangi et al 2018).…”
Section: Lulc Changes and Cropland Expansionsupporting
confidence: 68%
“…The hydrology and physical properties of dambos influence their ecological properties and the availability of ecosystem services (Adekola et al, 2012; Chatanga et al, 2019, 2020; Ondiek et al, 2020). Thus, changes in ecosystems triggered by changes in water availability influence the balance between different wetland species (Behn et al, 2018: Ondiek et al, 2020), and this is significant for the availability of different provisioning, regulating and supporting services. In addition, human activity in dambos also gives rise to environmental degradation and loss of biodiversity and these ecosystem services (Langan et al, 2019; Munishi and Jewitt, 2019; Owethu Pantshwa and Buschke, 2019; Orimoloye et al, 2020).…”
Section: Wetland Definitions and Typesmentioning
confidence: 99%
“…The hydrology and physical properties of dambos influence their ecological properties and the availability of ecosystem services (Adekola et al, 2012; Chatanga et al, 2019, 2020; Ondiek et al, 2020). Thus, changes in ecosystems triggered by changes in water availability influence the balance between different wetland species (Behn et al, 2018: Ondiek et al, 2020), and this is significant for the availability of different provisioning, regulating and supporting services.…”
Section: Wetland Definitions and Typesmentioning
confidence: 99%
“…76 In East Africa too, between 1966 and 2018, wetland areas fell by 55 percent, largely driven by agricultural development and the search for income-generating activities. 77 The resulting fragmentation and degradation of ecosystems and of biodiversity severely diminish the capacity of ecosystems to provide food, fresh water and genetic material and to play their environment-and climateregulating role.…”
Section: Ecology and Climatementioning
confidence: 99%